Résidence des élus et structures socioélectorales en Région de Bruxelles-Capitale - Christian Vandermotten (Brussels Studies)
The article begins by examining the residential pattern of supra-municipal elected representatives living in the Brussels-Capital Region and its recent development. It shows that this pattern tends to be more and more in keeping with that of the Brussels population as a whole, with however an over-representation of the most affluent neighbourhoods, where almost half of MR and DéFI elected representatives live, especially in the eastern part of the outer ring. CdH and Dutch-speaking elected representatives are more likely to live in the western part of the outer ring, but there has been a sharp increase in the number of Flemish elected representatives who live in the neighbourhoods of the poor area which are undergoing gentrification. The same is true for the green elected representatives, who are at the heart of the gentrification process in poor central neighbourhoods. Although the overwhelming majority of elected representatives from an immigrant background are still socialist, the residential pattern of socialist elected representatives shows a shift from the central neighbourhoods to the outer ring. As regards PTB elected representatives, they do not live in the poorest neighbourhoods so much as in middle-income areas, reflecting a highly politicised environment from the world of skilled labour. The article goes on to examine the coherency which can be observed between the geography of elected representatives and that of their electorate, based on the available data from the municipalities and elections at this level of power.